Prepancreatic postduodenal portal vein discovered in a pediatric patient undergoing total pancreatectomy with islet autotransplantation: a case report and review of literature - Colak, Muhammed Ali; Trout, Andrew T.; Heinzman, Christie; Freeman, A Jay; Rasmussen, Sara K.; Abu-El-Haija, Maisam; Nathan, Jaimie D. (Frontiers in Surgery, 2025)
BackgroundPrepancreatic postduodenal portal vein (PPPV) is a rare anatomic variant where the portal vein (PV) runs anterior to the pancreas and posterior to the duodenum. Only 20 cases of PPPV, all in adults, have been reported in literature. We report the first case of PPPV in a pediatric patient discovered intraoperatively during total pancreatectomy with islet autotransplantation (TPIAT) and the third known case in which the PPPV could be isolated intraoperatively.CaseA 10-year-old girl with debilitating acute recurrent pancreatitis requiring daily pain medication was admitted for elective TPIAT operation. Genetic workup for hereditary causes of pancreatitis was negative. Preoperative magnetic resonance cholangiopancreatography did not identify an abnormal course of the PV. During operation, dissection of tissues anteriorly overlying the pancreas revealed the variant PV anatomy. The PV was adherent to the anterior neck of the pancreas and coursed cranially posterior to the duodenum. Although prior reports have described PPPVs as thin-walled and fragile, the morphology and caliber of the PPPV appeared normal in our patient. The pancreas was adherent to and coursed between the PV and the superior mesenteric artery. The pancreas was meticulously dissected off the vessels and resected. The PPPV was successfully isolated and preserved for islet infusion later in the procedure. After isolation, 2/3 of islets were infused into the PV, and the remaining 1/3 were placed within the peritoneum due to persistently elevated portal venous pressures. There were no complications during the case, and the patient recovered as expected after operation.ConclusionOur case highlights the first reported case of PPPV in a pediatric patient and one of the three instances wherein it could be safely isolated intraoperatively. Recognition of such anatomic variations is crucial for the safety of operations such as TPIAT that include extensive vascular dissection in chronically scarred operative fields.